The Effect of Health Education with Audio Visual Media on Changes in Mother’s Behavior in Stunting Prevention - Suriani Ginting (Humanistic Network for Science and Technology (HNST), 2022)
Stunting in children is challenge in the development of quality Indonesian people. Number of stunting in Indonesia is still quite high, at 30.8 percent. In the 2020-2024 RPJMN, the suppression of the stunting rate is targeted to be 19% in 2024 from the current 30.8%. This study aims to determine and analyze the effect of health counseling with audio visual media on changes in mother's behavior in preventing stunting in Doloksanggul sub district, Humbang Hasundutan district in 2021. The method used in this study was quasi-experimental method with use of counseling as treatment. Delivery of information supported by provision of audio-visual media about stunting prevention. The population in this study were all couples of fertiled age women and it was conducted in May 2021. The sample in this study was used by part of the population of women of childbearing age in the Doloksanggul District, Humbang Hasundutan Regency in 2020, which was 148 people. The sample size in this study was calculated based on the Slovin formula (the sample size was 35 women of childbearing age). The instruments used were video audio visual media, respondent identity questionnaire and knowledge, attitude and practice questionnaire. Statistical analysis was carried out with the aim of explaining the relationship between the variables being studied, using paired sample t-test. The results of data processing showed that there was a significant difference between behavior in stunting prevention before counseling with audio-visual media and after counseling with a p-value of 0.000. Based on the results of the research that has been done, it can be concluded that there were significant differences in knowledge, attitudes and practices before and after intervention with audio-visual media. It is hoped that effectiveness and efficiency in delivering information will be carried out to mothers. The media provided is in form of files that can be repeatedly accessed via Android. The provision of audio-visual media adds learning tools in education, in addition to increase the ease of access to knowledge for the community. Keywords: counseling; audio visual; knowledge; attitude; practice; stunting